Study of the rs1800795 polymorphism of the IL6 gene to verify the clinical portrait of a patient with chronic heart failure: gender aspects - Elena V. Khazovа; Olga V. Boulashova; Elena V. Valeeva (Consilium Medicum, 2022)
Background. Genetic studies in cardiology allow to identify predisposition and predict the course of multifactorial cardiovascular diseases by identifying the association of polymorphic loci of candidate genes with the clinical phenotype. One of these diseases associated with poor prognosis is chronic heart failure (CHF). Activation of pro-inflammatory cytokines is one of the key aspects of the development and progression of CHF.